Pengaruh Strategi Co-Branding Terhadap Keputusan Pembelian Produk Kosmetik Emina di Kota Surabaya - Mutiara Fadhillah; Sugiharto Sugiharto; Bambang Karnain; Harsono Teguh Santoso; Achmad Daengs GS (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
After the Covid-19 pandemic, global challenges such as rising living costs, political uncertainty, energy crises, and extreme climate change have significantly affected various industries, including the beauty sector in Indonesia. In this competitive landscape, Emina Cosmetics seeks to maintain its relevance by adopting innovative management strategies, particularly through co-branding collaborations with well-known brands like Chatime. This study aims to analyze the influence of co-branding on consumer purchasing decisions. Data were obtained from 97 respondents using a purposive sampling technique. The analysis employed the Partial Least Square (PLS) method to examine the structural relationship between variables. The findings indicate that co-branding initiatives play a significant role in shaping consumer perceptions, enhancing brand attractiveness, and influencing purchasing decisions. These results highlight the strategic importance of co-branding as a marketing approach for companies in highly competitive markets, especially within the beauty industry.